Education of the stunting awareness movement in support of the Kubu Raya Regency Government program - Nuruniyah Nuruniyah; Pasmawati Pasmawati; Hasrialang Hasrialang; Yuyun Nisaul Khairillah (Community Empowerment, 2024)
Stunting is due to a lack of nutritional intake over a long period or chronically from the womb until the baby is born. Factors that trigger stunting include lack of access to clean water, poor sanitation and access to health services. Stunting awareness movement education is provided to support the Kubu Raya Regency government program to reduce stunting cases. The solution to the problem is education on the causes and effects of stunting, now and in the future. The stages of implementing PKM activities include planning, implementation and evaluation. The education provided has increased participants' understanding from 50% to 89%.